2010
DOI: 10.1167/iovs.10-5499
|View full text |Cite
|
Sign up to set email alerts
|

Intersubject Variability of Foveal Cone Photoreceptor Density in Relation to Eye Length

Abstract: The AOSLO can resolve the smallest foveal cones in certain eyes. Although myopia causes retinal stretching in the fovea, its effect within the foveola is confounded by factors other than cone density that have high levels of intersubject variability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
191
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(221 citation statements)
references
References 60 publications
28
191
1
1
Order By: Relevance
“…They reported that cone density was significantly lower in myopic eyes, although at a given location, there was considerable individual variation [39]. This intersubject variability was also reported by Li and collaborators [40]. Myopic eyes were found generally to have higher angular density near the foveal center.…”
Section: Discussionsupporting
confidence: 52%
“…They reported that cone density was significantly lower in myopic eyes, although at a given location, there was considerable individual variation [39]. This intersubject variability was also reported by Li and collaborators [40]. Myopic eyes were found generally to have higher angular density near the foveal center.…”
Section: Discussionsupporting
confidence: 52%
“…This variation in visual acuity is not surprising because of the inherent differences in foveal cone-packing density and the location of the steady fixation region between individuals. [7][8][9][10][11][12] Studies [13][14][15] have also shown that the receptive fields of the retinal ganglion cells limit spatial resolution outside the foveal pit, adding to the debate on whether there is a need to develop improved models of the human eye's visual performance.…”
mentioning
confidence: 99%
“…Características básicas do sistema detector (Burns et al, 2007), se ben polo momento non son abondo potentes como para resolver sempre os fotorreceptores máis pequenos da foveola, que é unha parte moi importante da retina. Os novos métodos por unha parte confirman os valores obtidos anteriormente, e por outra permiten estudar un número moi superior de retinas, véndose como afectan factores tales como a idade (Song et al, 2011), longura do ollo (Li et al, 2010), ametropía (Chui et al, 2008) ……”
Section: Unidade Didáctica VI Características Básicas Do Sistema Detunclassified